Active control of counter-rotating open rotor interior noise in a Dornier 728 experimental aircraft. (18th August 2016) - Haase, Thomas; Unruh, Oliver; Algermissen, Stephan; Pohl, Martin
Abstract: The fuel consumption of future civil aircraft needs to be reduced because of the CO2 restrictions declared by the European Union. A consequent lightweight design and a new engine concept called counter-rotating open rotor are seen as key technologies in the attempt to reach this ambitious goals. Bearing in mind that counter-rotating open rotor engines emit very high sound pressures at low frequencies and that lightweight structures have a poor transmission loss in the lower frequency range, these key technologies raise new questions in regard to acoustic passenger comfort. One of the promising solutions for the reduction of sound pressure levels inside the aircraft cabin are active sound and vibration systems. So far, active concepts have rarely been investigated for a counter-rotating open rotor pressure excitation on complex airframe structures. Hence, the state of the art is augmented by the preliminary study presented in this paper. The study shows how an active vibration control system can influence the sound transmission of counter-rotating open rotor noise through a complex airframe structure into the cabin. Furthermore, open questions on the way towards the realisation of an active control system are addressed. In this phase, an active feedforward control system is investigated in a fully equipped Dornier 728 experimental prototype aircraft. In particular, the sound transmission through the airframe, the coupling of classical actuators (inertial and piezoelectric patch actuators) into the structure and the performance of the active vibration control system with different error sensors are investigated. It can be shown that the active control system achieves a reduction up to 5 dB at several counter-rotating open rotor frequencies but also that a better performance could be achieved through further optimisations.